Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1017/s1463423617000159
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of primary care chaplaincy compared with antidepressants: a retrospective study comparing chaplaincy with antidepressants

Abstract: This was a retrospective observational study based on routinely collected data. There were 107 patients in the PCC group and 106 in the antidepressant group. Socio-demographic data were collected. Their pre- and post-intervention (either chaplaincy or antidepressant) well-being was assessed, by the Warwick-Edinburgh Mental Well-being Scale (WEMWBS) which is a validated Likert scale. Findings The majority of both groups were female with both groups showing marked ethnic homogeneity. PCC was associated with a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 37 publications
3
24
1
Order By: Relevance
“…3 Research has shown that such chaplaincy provision improves spiritual wellbeing to a similar extent as antidepressants while reducing GP consultation rates. 4,5 These results justify the place of chaplaincy within our MDTs at this time of workload realignment.…”
Section: Spiritual Care Is Stagnating In General Practicesupporting
confidence: 64%
See 1 more Smart Citation
“…3 Research has shown that such chaplaincy provision improves spiritual wellbeing to a similar extent as antidepressants while reducing GP consultation rates. 4,5 These results justify the place of chaplaincy within our MDTs at this time of workload realignment.…”
Section: Spiritual Care Is Stagnating In General Practicesupporting
confidence: 64%
“…Personal continuity of care has been shown to improve patient outcomes, 4 and in building mutually trusting relationships between doctor and patient is likely also to offer greater professional satisfaction. (Think cine films versus albums of random snapshots!…”
Section: The Resilient General Practice: Working As a Packmentioning
confidence: 99%
“…The study was observational with no randomisation or allocation occurring. This study was a continuation of previously published data (Macdonald, 2017a), with data collection occurring between March 2015 and July 2017. This generated a further 11 months of data and allowed a more comprehensive analysis of above objectives.…”
Section: Methodsmentioning
confidence: 96%
“…Patients attending PCC have a wide variety of symptoms triggered by a multifaceted interaction between the physical and the spiritual. Often these are expressed in an undifferentiated manner, that is in terms of loss of well-being as distinct but somewhat less tangible than depression or anxiety (Macdonald, 2017a). Such undifferentiated illnesses often present with more than one issue or symptom (Green and Holden, 2003), and this is the experience in PCC.…”
Section: Undifferentiated Illnessmentioning
confidence: 99%
“…Kevern and Hill (2015) used survey methods to show that chaplains improved the wellbeing of people in primary care. In a retrospective review, Macdonald (2017) found primary care chaplains to be as effective as antidepressants. All these authors concluded that the next step for chaplaincy research is to measure outcomes of chaplaincy interventions.…”
Section: Introductionmentioning
confidence: 99%